Coppice and high forest Eucalyptus stands show similar drought resistance on deep soils - Costa, Jenickson R S [UNESP]; Maciel, Jhuan L M [UNESP]; Silva, Magali R [UNESP]; Campoe, Otávio C [UNESP]; le Maire, Guerric; Alvares, Clayton A [UNESP]; Martin-StPaul, Nicolas K; Bittencourt, Paulo; Pereira, Luciano; Cagnoni, Leticia B; Laclau, Jean-Paul; Nouvellon, Yann; et al. (Oxford University Press (OUP), 2025)
Increasing drought under climate change is affecting forests worldwide, raising concerns about management strategies for sustainable wood production. Eucalyptus, the dominant genus in hardwood plantations, can be managed as either coppice or high forest stands, yet the effects of this silvicultural decision on water stress and drought resistance remain largely unexplored. If coppice trees experience reduced water stress during their early growth due to the surviving deep root apparatus from the previous rotation, they may exhibit traits that are less adapted to drought survival. Here, we measured structural stand features (leaf area index, LAI; standing biomass), dehydration-resistance traits (leaf turgor loss point, Ψtlp; xylem vulnerability to embolism, Ψ50), in situ water stress (minimum leaf water potential, Ψmin) and metrics of drought-mortality risk (hydraulic safety margins, HSM) to compare the drought resistance and productivity of 10 Eucalyptus clones growing in deep soils under both high forest and coppice silvicultural treatments in a common garden in southeastern Brazil. Biomass at mid-rotation (3 years after planting) was on average 15% greater in coppice stands, associated with a 32% greater LAI across Eucalyptus clones. Standing biomass of clones grown in coppice could not be predicted from that of high forests. Water stress, drought resistance traits and drought-mortality risks were similar between silvicultural treatments. Some traits (LAI, Ψtlp, Ψ50, Ψtlp-based HSM) exhibited a consistent clonal ranking in both silvicultural treatments, while other traits (Ψmin, Ψmin-based HSM) did not. The hydraulic system of Eucalyptus trees does not plastically respond to coppicing, making coppice a viable option for Eucalyptus management under drought, if appropriate clonal selection is implemented. However, selecting drought-resistant and productive coppice clones based on high forest data should be considered with caution.